Pengaruh Layanan Informasi Karier dan Dukungan Orang Tua Terhadap Minat Melanjutkan Studi Ke Perguruan Tinggi - Anggraini, Lisa; F, Firman; N, Netrawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Education plays an important role as the spearhead in determining the future of the nation, without education there will be no successor to the noble ideals to achieve the welfare and progress of the nation. Through quality education, society has a role in making changes and national development. Quality education can be achieved through Elementary School, Middle School, High School and Up to College. Education is useful for keeping up with the development of knowledge and technology. Students’ interest in continuing their studies to college is an important factor in determining the success of higher education. Factors that influence this interest include career information services and parental support. Effective career information services can provide insight and motivation for students in choosing an educational path that suits their interests and talents. Parental support, both emotionally and materially, also plays an important role in shaping students’ decisions to continue their studies to college.